Distribution and Abundance of Zooplankton in Fitu Waters, Ternate North Maluku - Yuliana, Yuliana; Mutmainnah, Mutmainnah; Ahmad, Khamsiah; Sabar, Mesrawaty; Surahman, Surahman; Djamhur, Martini (Agrikan Jurnal Agribisnis Perikanan, 2024)
This study aimed to analyze the distribution and abundance of zooplankton in Fitu waters Ternate. The research was carried out from March to April 2023. Sampling was conducted 4 (four) times at 5 (five) stations. The method for collecting zooplankton is done by filtering 30 liters of water, the filtered results are then preserved using 4% Lugol's solution. The research results show that the zooplankton have a wide distribution of the genus Brachionus. Meanwhile, the types found only once during the research were Acanthostomella, Dictyocysta, Didinium, Favella, Loxophyllum, Paravafella, Parundella, Calanopia, Centropages, Halocypris, Paracalanus, Sarsia, Gazelletta, and Fritillaria. The composition of zooplankton species is dominated by the Crustacea group with a percentage of 33% and the lowest are the Urocohordata and Hydrozoa groups with only 3% each. The number of zooplankton genera found was 36, originating from 8 groups, namely Ciliata (14 genera), Crustacea (11 genera), Hydrozoa (2 genera), Rotifera (1 genus), Sagittoidea (1 genus), Sarcodina (5 genera), and Urocohordata (2 genera). The zooplankton abundance obtained was included in the high category, with a range of 3285 - 12350 ind.L-1. For the ecological indices, the diversity index (H') was 1.0047 - 2.1747, the evenness index (E) was 0.5607 - 0.9207, and the dominance index (D) was 0.1728 - 0.5405.